Map Υour Circle by Νατάσσα Παππά (GR) - Mouzouropoulos, Theseas (My University, 2026)
This workshop was held by Νατάσσα Παππά (GR) which she was a guest speaker in the 1st Graphic & Illustration Design Conference [GRID19]